Assessing collaboration networks in educational research: A co-authorship-based social network analysis approach. Issue 3 (11th April 2016) - Munoz, David Andres; Queupil, Juan Pablo; Fraser, Pablo
Abstract : Purpose: – The purpose of this paper is to analyze collaboration networks and their patterns among higher education institutions (HEIs) in Chile and the Latin American region. This will provide evidence to educational managements in order to properly allocate their efforts to improve collaboration. Design/methodology/approach: – This quantitative study examines collaboration using a social network analysis (SNA) approach. The main source used to quantify collaboration is co-authorship of scholarly publications retrieved from the Web of Science scientific search engine. Findings: – The paper provides evidence that there is a low collaboration rate within-country as well cross-country among HEIs in Latin America. The collaboration network in Chile is highly dependent on two institutions; Pontificia Universidad Católica and Universidad de Chile. These institutions are considered leaders of opinion and knowledge facilitators. The density of the whole network is relatively low; only 5 percent of the potential connections exist in the current network. Research limitations/implications: – The main limitation of this paper is that it does not take into account other possible collaborative efforts such as books, manuscripts, or other types of collaboration that do not result in tangible documents. However, co-authorship based on publications has been considered to be a good estimator of collaboration. Practical implications: – Collaboration is critical to promote research and increase its capacity. The approach presented in this study is helpful for educational managers in charge of allocating resources to effectively have an impact on collaboration. Decision makers will benefit from the evidence-based results generated by the SNA framework. Originality/value: – An understanding of the current status of research collaboration in Latin America allows researchers to detect the main areas of opportunity, which in turn serve to improve future decision making in this area.